2022
DOI: 10.1111/ppe.12857
|View full text |Cite
|
Sign up to set email alerts
|

Multifoetal gestations mediate the effect of in vitro fertilisation (IVF) on ischaemic placental disease in autologous oocyte IVF more than donor oocyte IVF

Abstract: Background Ischaemic placental disease (IPD) affects 16%–23% of pregnancies in the United States. In vitro fertilisation (IVF) is a risk factor for IPD, and the magnitude of increase in risk differs for individuals using donor oocytes (donor IVF) versus their own oocytes (autologous IVF). In addition, multifoetal gestations, which are more common in IVF than non‐IVF pregnancies, also are a risk factor for IPD. Objective To quantify the contribution of multifoetal gestations to the association between IVF and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Further exploration of the differences in IPD endometrial protocols in IVF is essential both for understanding the underlying biology and for identifying targets for future research. IPD shares the same pathogenesis as pre-eclampsia, placental rupture, and SGA [ 15 ]. It is widely accepted that in some pregnancies affected by pre-eclampsia, placental development is disrupted, leading to cellular, molecular, immune, and vascular changes, and that the role of insufficient decidualization has also received increasing attention, especially in vascular pathology [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration of the differences in IPD endometrial protocols in IVF is essential both for understanding the underlying biology and for identifying targets for future research. IPD shares the same pathogenesis as pre-eclampsia, placental rupture, and SGA [ 15 ]. It is widely accepted that in some pregnancies affected by pre-eclampsia, placental development is disrupted, leading to cellular, molecular, immune, and vascular changes, and that the role of insufficient decidualization has also received increasing attention, especially in vascular pathology [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This association was largely due to the lower risk of placental insufficiency during the frozen embryo transfer cycle. Another study showed an increased risk of IPD after donating oocyte fertilization in vitro [ 14 , 15 ]. However, the effect of the protocol during endometrial preparation on IPD has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…When compared against IVF conceived with autologous oocytes, pregnancies from OD have shown lower placental volumes at the first trimester (27), a different uterine perfusion profile across gestation (28,29), higher rates of villitis of unknown etiology (VUE) (30) and also an increased risk of preeclampsia (14,26) and placental related disease in the third trimester (14,17,(31)(32)(33).…”
Section: Donated Oocytes Perinatal Outcomes and Placental Dysfunctionmentioning
confidence: 99%
“…Interestingly, some reports comparing pregnancies from oocyte donation with those conceived with autologous oocytes have shown in the former group lower placental volumes at the first trimester [17], a different uterine perfusion profile across gestation [24,25], and higher rates of preeclampsia [7] and villitis of unknown etiology [26]. Moreover, recent studies have shown an increased risk of placental pathology in the third trimester, especially among pregnancies after oocyte donation [7,12,[27][28][29]. Overall, these findings suggest mechanisms related to progressive placental dysfunction, rather than abnormal placentation.…”
Section: Introductionmentioning
confidence: 99%